Palingenius Zodiacus vitae-je a magyarországi Album Amicorumokban - Knapp, Éva (Antikvitás & Reneszánsz, 2018)
The reception history of the Zodiacus vitae is an independent research topic long ago outside Hungary, researchers have been analyzing the various levels and forms of reception for decades. However, the peculiarities of the Palingenius-reception in Hungary have not been systematically studied. Although full edition of the entire Zodiacus vitae printed in Hungary is not known, several copies of different printed editions arrived to Hungary. The popularity of this epic philosophical poem is indicated by several entries in the autograph albums of peregrine students. These Hungarianrelated entries mostly accurately quote the details of the work in gnomes. The conscious, customized combination and re-functioning of quotations follows the international practice of the era.